BODIPY and porphyrin dyes for direct glucose sensing and optical limiting applications - Ndebele, Nobuhle (Rhodes University, Faculty of Science, Department of Chemistry, 2019)
A series of BODIPY dyes functionalised with boronic acid in the 3,5-positions were successfully synthesised and characterised by using various analytical techniques. The dyes were prepared through a slight modification of the conventional acid catalysed condensation method. Phenylboronic acid moieties were added as styryl groups at the 3,5-positions of the 1,3,5,7-tetrametylBODIPY cores using a modified Knoevengal condensation method. The addition of the styryls resulted in the main absorption band of the dyes red-shifting to the 630âˆ’650 nm region. The photophysical and electrochemical properties of these dyes were studied to determine whether the dyes are suitable for use in the fluorescent, colourimetric and electrochemical detection of glucose. Boronic acid moieties were added as bioreceptor recognition elements because they have an affinity for carbohydrates and therefore would be able to bind and "detect" glucose. The series of BODIPY dyes did not show a "turn-on" fluorescence effect upon addition with glucose at the physiological pH. This was attributed on the basis of molecular modelling to the absence of an MO localised on the boronic-acid-substituted styryl moieties that lie close in energy to the HOMO and LUMO that facilitates the formation of an intramolecular charge transfer state. However, colourimetric changes that are visible to the naked eye are observed at basic pH when glucose was added to the dye solutions. The dyes exhibited favourable electrochemical behaviour and were able to detect glucose directly in this context when glassy carbon electrodes are modified through the drop dry method. A series of Sn(IV) porphyrins with thienyl and phenyl groups at the meso-positions were successfully synthesised and characterised. Pyridine and tetrabutyl axial ligands were added to the porphyrins to limit aggregation. The optical limiting properties of these porphyrins and three styrylated BODIPY dyes were studied in benzene and dichloromethane. Dyes were also embedded in polystyrene and studied as thin films to further gauge their suitability for use in optical limiting applications. Second-order hyperpolarizability, third-order susceptibly, non-linear absorption with reversible saturable absorption and the optical limiting threshold, were the parameters studied. Three of the four porphyrins and the three styrylated BODIPY dyes showed favourable optical limiting behaviour, which was further enhanced when the dyes are embedded in polymer thin films.
Keywords: Boron compounds; Boric acid; Porphyrins; Dyes and dying -- Chemistry